Penerapan Platform Edmodo di Perguruan Tinggi: (Sebuah Survey di STKIP Muhammadiyah Bogor) - Musaljon musaljon (Jurnal Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2020)
Nowadays, social media has become an integral part of student life, they use social networking sites to connect with friends and family. This study involved enhancing student learning experiences facilitated through social networking sites for educational purposes called Edmodo. This study aims to explore students' perceptions about the use of Edmodo as a complementary tool in learning. At the end of the lecture, 94 students who participated in this study completed a 5-Likert-scale survey questionnaire containing 30 items and 4 open-ended questions online. The findings reveal that Edmodo is considered a useful and beneficial learning tool for addressing deficiencies in face-to-face traditional classrooms because it provides various features that support student learning processes. As support for learning, Edmodo is considered an effective learning tool because it increases student motivation, flexibility, and participation in online learning activities. Further research is suggested on the use of Edmodo in students with different educational levels, cultural backgrounds and learning styles. These findings prove the pedagogical advantages of developing and designing blended learning classes.